201Thallium Scintigraphy – a New Method for Radionuclide Imaging of the Uterus - Pertyński, T.; Zimmermann, P.; Reuter, D. Th.; Hundeshagen, H. (Nuklearmedizin - NuclearMedicine, 1977)
A new radionuclide method for uterus imaging is described. After intravenous application of 201T1 chloride the myometrium can be displayed by means of a gamma camera and a small digital computer. Early results suggest that T1 accumulation by the uterus depends on its histopathologic structure. After intra-uterine injection of 133Xe in saline demarcation between myometrium and uterine cavity is possible.